Phloem transport in gymnosperms: a question of pressure and resistance. (June 2018) - Liesche, Johannes; Schulz, Alexander
Graphical abstract: Highlights: Phloem flow in gymnosperms experiences more resistance than in angiosperms. Sieve elements are coupled by plasmodesma-like sieve pores with elaborate ER system. Phloem transport is slower than in angiosperm trees, but compatible with Münch. Lateral unloading to and reloading from the ray system plays a significant role. Sieve area ER and lateral unloading–reloading might regulate phloem transport. Abstract : Even in the highest trees, carbon is efficiently distributed from leaves to heterotrophic tissues like fruit, flowers and roots. This long-distance transport happens in the highly specialized sieve elements of the phloem. In gymnosperms, sieve element anatomy appears to be less suited for mass flow of phloem sap than that of angiosperms. This review covers available data on gymnosperm phloem to evaluate if it functions differently from that of angiosperms. Although current evidence suggests that, despite a higher pathway resistance, a single source-to-sink turgor pressure gradient can drive mass flow, several questions remain unanswered. These include how endoplasmic reticulum-complexes in sieve elements influence flow, as well as what the effect of symplasmic coupling along the whole phloem pathway could be.